Reaction Kinetics of One-Pot Xylan Conversion to Xylitol via Precious Metal Catalyst - Hilpmann, Gerd; Kurzhals, Pascal; Reuter, Tom; Ayubi, Mick Miro (Frontiers in Chemical Engineering, 2020)
The hydrolytic hydrogenation of xylan to xylitol by a one-pot process was studied en detail in a batch reactor. The reaction was catalyzed by a combination of dilute sulfuric acid and precious metal Ru on carbon powder. Process parameters were varied between 120 – 150 °C, while maintaining constant hydrogen pressure at 20 bar and acid concentration equivalent of pH 2. The xylan solution consisted of 1 wt.-% beechwood powder (Carl Roth, > 90%) in deionized water. Sulfuric acid was added to the solution until pH 2 was reached, then the 0.3 wt.-% catalyst powder (5 % Ru on Act. C) was added and the solution was put into the batch reactor. The first approach of kinetic modelling began with conventional 1st-order kinetics and compared this to a more complex model based on Langmuir-Hinshelwood kinetics. The xylan and xylitol data reached a good fit. However, the modelling results also showed that the rate-limiting step of xylose-formation was still not represented in a satisfactory manner. Therefore, the model was adapted and developed further. The advanced model finally showed a good fit the intermediate product xylose and the target product xylitol. The overall modelling methods and results are presented and discussed.